Autopsi dan Kejanggalan Hukum dalam Pembuktian Kasus Mirna: Tantangan dan Rekomendasi Reformasi Hukum (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2023)
The Mirna Salihin case has become one of the most horrendous events in the Indonesian legal system. On January 6, 2016, a young woman named Mirna Salihin died mysteriously after drinking coffee at a prestigious cafe in Jakarta. Mirna's tragic death shocked the public and became the center of media attention, raising big questions about the cause of death as well as whether an autopsy should be performed to uncover the real truth. The Mirna Salihin case became controversial due to the allegation that Mirna's death was caused by cyanide poisoning, a deadly poisonous substance. The fundamental question arises: What is the role of autopsy in solving murder cases? This triggers a conflict of dissent that must be explained and understood in greater depth. This journal aims to shed light on the key evidentiary challenges posed by autopsy irregularities, and provide insight into how this case became a dilemma for the legal process. The research utilized qualitative methods by collecting data from media news analysis. The final conclusion highlights important warnings about the difficulties and the need for change in the law enforcement and forensic systems.